2015
DOI: 10.1097/yct.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Sweden 2013

Abstract: ObjectivesThe use of electroconvulsive therapy (ECT) varies across countries. The aim of this study was to describe and explore the use of ECT in Sweden in 2013.MethodsThe Swedish mandatory patient register of the National Board of Health and Welfare includes information on diagnoses and treatments, including ECT. All 56 hospitals that provide ECT in Sweden also report to the nonmandatory national quality register for ECT, which contains information on patient and treatment characteristics. In this study, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 27 publications
1
36
0
12
Order By: Relevance
“…Recent reports in international settings 1115 show a wide variation in the prevalence of ECT use, with recent treated prevalence estimates ranging from 41 ECT patients/100,000 population in Sweden 11 to 1.1 ECT patients/100,000 population in Poland 2 . A recent systematic review and meta-analysis on the use of ECT internationally only included US studies dating from 1999 or earlier as no more recent studies were available 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports in international settings 1115 show a wide variation in the prevalence of ECT use, with recent treated prevalence estimates ranging from 41 ECT patients/100,000 population in Sweden 11 to 1.1 ECT patients/100,000 population in Poland 2 . A recent systematic review and meta-analysis on the use of ECT internationally only included US studies dating from 1999 or earlier as no more recent studies were available 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Case et al (10) reported that the total number of hospitals offering ECT has been declining. In international settings, ECT utilization varies widely across regions, with utilization estimates ranging from 1.1 ECT patients per 100,000 people in Poland (11) to 41 ECT patients per 100,000 people in Sweden (12). The most recent utilization estimates for the procedure in the United States date to 1999 or earlier (13) and vary widely by region, ranging from eight ECT patients per 100,000 people in California (14) in 1995 to 42 ECT patients per 100,000 people in New England in the same year (15).…”
mentioning
confidence: 99%
“…Electroconvulsive therapy (ECT) was not included in the STAR*D-study, but is a well-established treatment for severe depression. In Sweden – a country with 9.5 million inhabitants – ∼4000 patients per year receive ECT ( 6 ). With repeated administrations, ECT is highly effective in relieving depressive symptoms: The percentages of patients achieving remission in two recently completed clinical trials was 64% ( 7 ) and 60% ( 8 ), respectively, although the results may be less favourable in clinical practice ( 9 ).…”
Section: Introductionmentioning
confidence: 99%